Forms of intertextuality in the novel of M. Z. Danielewski and J. S. Foer - Kashkan, Tatsiana A. (Journal of the Belarusian State University. Philology, 2023)
The forms of intertextuality in the novels of modern American writers M. Z. Danielewski («House of leaves») and J. S. Foer («Here I am», «The tree of codes», «Extremely loud and incredibly close», and «Everything is illuminated») are investigated. The aim of the work is to identify and systematise the following references in the works: allusion, reminiscence, title and epigraph. To do this, the author creates a classification in which these forms are referred to biblical, literary, mythological, cultural and linguistic precedent texts. It is shown that M. Z. Danielewski more often turns to literary precedent texts, while J. S. Foer refers to biblical ones. Special attention is paid to the study of the functions of allusions, reminiscences, titles and epigraphs in the studied novels.
Keywords: forms of intertextuality; allusion; reminiscence; title; epigraph; precedent text; recipient text